2013
DOI: 10.1055/s-0033-1338705
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Direct Vinylogous Michael Addition of γ-Aryl-Substituted Deconjugated Butenolides to Nitroolefins and N-Phenylmaleimide

Abstract: Direct asymmetric vinylogous Michael reactions of γ-aryl-substituted deconjugated butenolides with nitroolefins and Nphenylmaleimide are described using bifunctional thiourea derivatives as the catalyst. The resulting butenolide derivatives containing adjacent quaternary and tertiary stereocenters are obtained in good yields (54-90%) and with excellent enantioselectivities (er up to 99:1) and high diastereoselectivities (dr up to >20:1).Owing to their widespread occurrence as substructures in various natural p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“… [56] The reaction was found to be equally effective for butenolides bearing linear alkyl chains, branched alkyl groups or benzyl substrates. Further it was also extended with γ‐aromatic substituted butenolides [57] . Overall, the reaction proceeded well to produce several γ‐substituent butanolide adducts 62 bearing a quaternary stereogenic centre adjacent to the oxygen with very high yields, diastereoselectivities and enantioselectivities (up to 99 % yield, 18 : 1 d.r.…”
Section: Organocatalytic Asymmetric Conjugate Additions To Maleimidesmentioning
confidence: 90%
See 1 more Smart Citation
“… [56] The reaction was found to be equally effective for butenolides bearing linear alkyl chains, branched alkyl groups or benzyl substrates. Further it was also extended with γ‐aromatic substituted butenolides [57] . Overall, the reaction proceeded well to produce several γ‐substituent butanolide adducts 62 bearing a quaternary stereogenic centre adjacent to the oxygen with very high yields, diastereoselectivities and enantioselectivities (up to 99 % yield, 18 : 1 d.r.…”
Section: Organocatalytic Asymmetric Conjugate Additions To Maleimidesmentioning
confidence: 90%
“…Further it was also extended with γ-aromatic substituted butenolides. [57] Overall, the reaction proceeded well to produce several γ-substituent butanolide adducts 62 bearing a quaternary stereogenic centre adjacent to the oxygen with very high yields, diastereoselectivities and enantioselectivities (up to 99 % yield, 18 : 1 d.r. and > 98 % ee).…”
Section: Asymmetric Conjugate Additions Using γ-Aryl-substituted Deco...mentioning
confidence: 90%
“…Michael addition reactions of butenolides 17 with electrophiles 18 using the slightly modified urea catalyst 2H has been reported by Mukherjee’s group (Scheme 33 ). 79 Using this protocol the authors demonstrated the enantioselective vinylogous 1,4-addition of γ-aryl-substituted deconjugated butenolides 17 with nitroolefins 18 . The main reason for the reduced catalyst loading is the presence of a highly reactive aryl group in the deconjugated butenolides.…”
Section: Hydrogen-bonding Catalysismentioning
confidence: 99%